Morphine interaction with prasugrel: a double-blind, cross-over trial in healthy volunteers - Hobl, Eva-Luise; Reiter, Birgit; Schoergenhofer, Christian; Schwameis, Michael; Derhaschnig, Ulla; Lang, Irene Marthe; Stimpfl, Thomas; Jilma, Bernd (Clinical research in cardiology, 2016)
Background Morphine decreases the concentrations and effects of clopidogrel, which could lead to treatment failure in myocardial infarction. Objectives To clarify whether more potent P2Y 12 -inhibitors may provide an effective alternative, we examined drug–drug interactions between morphine and prasugrel. Methods Twelve healthy volunteers received 60 mg prasugrel with placebo or 5 mg morphine intravenously in a randomized, double-blind, placebo-controlled, cross-over trial. Pharmacokinetics were determined by liquid chromatography tandem mass spectrometry, and prasugrel effects were measured by platelet function tests. Results Morphine neither diminished total drug exposure (AUC), which was the primary endpoint, nor significantly delayed drug absorption of prasugrel. However, morphine reduced maximal plasma concentrations ( C max ) of prasugrel active metabolite by 31 % ( p = 0.019). Morphine slightly, but not significantly, delayed the onset of maximal inhibition of platelet plug formation under high shear rates (30 vs. 20 min). Whole blood aggregation was not influenced. Conclusions Although morphine significantly decreases the maximal plasma concentrations of prasugrel active metabolite, it does not diminish its effects on platelets to a clinically relevant degree in healthy volunteers. However, it should be considered that the observed decrease in C max of prasugrel active metabolite caused by morphine co-administration may gain relevance in STEMI patients. Clinical Trial Registration : NCT01369186, EUDRA-CT#: 2010-023761-22.